Phenolic Compounds of Sponge-associated Fungi (Lecanicillium evansii) - HEFNI EFFENDI (Microbiology Indonesia, 2012)
This study was chiefly aimed at pursuing new biologically active secondary metabolites of microfungus species, Lecanicillium evansii, isolated from sponge Callyspongia sp collected from West Bali Sea, Indonesia. Sponges were collected by scuba diving. A tiny piece of sponge was inoculated on the surface of malt agar plates and incubated at 27 ºC. In order to get a pure mono-culture of the fungus, repeated sub-culturing onto fresh malt agar plates were performed. The collected fungi were maintained on malt agar plates using the Wickerham medium. Mass cultivation of the fungus L. evansii (10 L) was carried out in 30 erlenmeyer flasks in Wickerham medium. After 10 days incubation, without shaking under constant room temperature (20 ºC), fungal mycelium were separated from the culture broth. The mycelia were extracted with methanol and ethyl acetate was added to the media. Both methanol-added mycelia and ethyl acetate-added media were left overnight. Seven compounds were isolated from L. evansii. Those compounds comprised phenolic compounds (terphenylin, deoxyterphenylin, terprenin 2, terprenin epoxide), bipeptide (cyclo-tyrosylprolyl), and simple aromatic compounds (acetyl hydroxybenzamide, 4-hydroxybenzaldehyde). Detailed analysis by NMR and mass spectrometry enabled their identification to be new deoxyterphenylin, new terprenin 2, and new terprenin epoxide.